Dictionary of Development Economics / Economic Terminology in three Languages English - French - German - Scharf Traute (Elsevier Publishing Company, 1969)
Introduction, Language Indication, Basic Table, Development, Planning, Agriculture, Industry, Transport and Communication, Communication, Investments and Financing, Finance and Taxes, Trade, Education and Training, Population and Manpower, Economic Ethnology, Development Statistics, Index.